Pengaruh Proses Pengolahan pada Warna dan Tekstur Daging Babi dan Daging Celeng - Muhammad Idris; Lia Amalia; Aji Jumiono; Erna Puspasari; Mardiah Mardiah (Jurnal Ilmiah Pangan Halal, 2026)
Authentication of non-halal meat is essential to ensure product integrity and prevent adulteration in meat-based foods. This study aimed to analyze the effect of processing methods on the texture and color characteristics of pork and wild boar meat as a basis for authentication. Samples of thigh meat were subjected to boiling, frying, and roasting. Texture properties (hardness, springiness, cohesiveness, gumminess, and chewiness) were measured using a Texture Analyzer, while color parameters (L*, a*, b*, chroma/C*, and hue angle/h) were determined using a Chromameter. Data were analyzed using a 2 × 3 factorial completely randomized design with analysis of variance (ANOVA), followed by Duncan’s Multiple Range Test (DMRT) at a 5% significance level. The results showed that processing methods had no significant effect on all texture parameters, whereas meat type significantly affected cohesiveness and gumminess, with higher values observed in wild boar meat. For color parameters, meat type significantly influenced L* and h, while processing methods significantly affected L*, a*, b*, and C*. Frying was identified as the most influential method in modifying color, as indicated by decreased lightness and increased redness, yellowness, and color intensity. Overall, texture and color parameters demonstrate strong potential as physical indicators for differentiating pork and wild boar meat after processing.